The White Tiger (2021): Lower Caste Identity and Character Development - Dliaulkhaq, Muhammad Khadziq; Christina, Christina (Faculty of Language and Literature, Universitas Sains Al-Qur'an, 2024)
This study is aimed to analyse: (1) the portrayal of lower caste people in India in The White Tiger (2021) movie, and (2) the psychological transformation of the protagonist presented in The White Tiger (2021) movie. The researcher uses the qualitative method to examine the problem. The object of this study is movie The White Tiiger (2021). The data used in this study is collected by the researcher through some steps, namely watching and reading, identifying, classifying, and selecting. In order to answer the problem statement and draw a conclusion from this study, the selected data is analyzed by the researcher through some steps, namely displaying, explaining, and interpreting. The approach and theory that the researcher uses to analyze the problem is sociology of literature and psychology of literature. The result of this study shows that (1) the portrayal of lower caste as portrayed by the lower caste characters of The White Tiger (2021) movie are depicted through various occurences including poor living condition, unfair treatment and bound by traditions (2) the personality change of the protagonist makes him change from a loyal servant to a disloyal servant.